Tra parola e immagine: prospettive estetiche nella poetica di Paul Ricœur (ENTHYMEMA, 2013)
Ricœur is not usually considered relevant in the field of figurative arts. However, the notion of imagination constitutes a crucial thread which is possible to detect in his production. This thread can supply significant hints not just for aesthetical thought, but also for interpretations of Ricœur’s thought. This emerges clearly in connection with studies on metaphor, where a particular position by Ricœur surfaces on the philosophy of images which steer clear from psychological interpretations. The French philosopher’s new interpretations connecting metaphorizing and creative imagination, allow not only to connect this issue with Ricœur’s other positions on art, but also offers some significant hints concerning the relationship with the social other – in the interweaving of ideology and utopia – and with the absolute other of religious transcendence.